Magical genealogies in cuir narratives. A memory made of fictions (Anclajes, 2026)
The aim of this work is to consider how literature can also be a space fo rconstructing memories queer alternative to those of the official story, that is, how fiction is a tool for weaving valid and powerful genealogies outside the codes of reality. To enter there, we open two paths that will end up crossing each other. First, we trace what could be a genealogy of queer genealogies, that is, we compile and congregate the concepts with which the processes of queerification of memory have been named. Second, we propose to think of literature as a queer counter-archive of dissident genealogies that uses fiction to create ecosystems and memories, moving away from traditional archival and historiographical practice; opposing, then, the violence of imposed silence and giving way to a whole lineage that moves through the imagination and has magical effects, like the legends that are told out loud.
Keywords: Genealogy; Queer; Memory; Counter-archiving